Performance of Fiber Self Compacting Concrete at High Temperatures - Helal Hameed Yahy AL-Radi; Shen Dejian; Hussein Kareem Sultan (Salehan Institute of Higher Education, 2021)
The goal of this study is to assess the fresh and hardened properties of self-compacting concrete (SCC) prepared using locally available materials. This research includes also the impact of polypropylene (PP), steel and hybrid fibers on the same properties. In addition, the mechanical properties of SCC specimens (with and without fibers) at high temperatures, including as compressive, tensile, and flexural strengths, will be determined. Four different SCC mixtures (with and without fibers) are prepared, tested, and assessed in order to attain these goals. The specimens were heated to various temperatures (200, 400, 600, and 800) at a rate of 5 degrees Celsius per minute for each test. The temperature was remained constant at the target temperature for one hour before cooling to ensure a consistent temperature throughout the specimen. According to the test results, all of the mixes have good consistency and workability in terms of filling and passing ability. In addition, the inclusion of fibers lowered the workability of SCC slightly. Also, the compressive, tensile, and flexural strengths improved with increasing temperature up to 200 °C and dropped at temperatures over 200 °C, according to these findings. Within the SCC, the PP fibers lowered and removed the risk of spalling. Concrete mixtures containing steel fibers and hybrid fibers have the finest mechanical characteristics and spalling resistance as temperature rises. Weight losses were lower in SCC mixtures with PP and steel fibers than in those without PP and steel fibers. As the temperature rose, all SCC mixes lost mass and UPV decreased until the samples spalled (as in plain SCC and SCC with steel fibers) or were questionable (as in SCC with PP and SCC with hybrid fibers). Doi: 10.28991/cej-2021-03091779 Full Text: PDF